An economic overview of Populus spp. in Short Rotation Coppice systems under Mediterranean conditions: An assessment tool for decision-making. (November 2021) - Fuertes, A.; Oliveira, N.; Cañellas, I.; Sixto, H.; Rodríguez-Soalleiro, R.
Abstract: Poplar Short Rotation Coppices can provide lignocellulosic raw material, promote employment in rural areas, contribute to achieving a low carbon bioeconomy and supply environmental benefits. Nevertheless, the economic feasibility of these plantations is a matter of concern and hampers the expansion of commercial initiatives. In this regard, this work aims to identify the most critical cost factors of poplar plantations under Mediterranean conditions. Data from an extensive network located at 30 different sites were used, in particular, detailed cost data for 2 rotations was available for 6 sites within the network. This study evaluates the critical factors that affect profitability, analysing the influence of the discount rate and biomass price under two productive scenarios derived from the network and evaluated as green biomass yield for the first rotation: Baseline (30.56 Mg ha −1 yr −1 ) and an Optimum (56.52 Mg ha −1 yr −1 ). Net Present Value after 12 years (4 rotations of 3 years each), ranges from −1105.54 € ha −1 (Baseline) to 9620.30 € ha −1 (Optimum). According to the findings of this study, profitability of poplar plantations will be achieved by ensuring optimum productivity, through an increase in current market prices (40 € Mg -1 ) or by valuing the ecosystem services, which are not currently quantified. Sensitivity analyses were performed for the most critical cost factors: land rent (31.88 %), irrigation (16.61 %), and cut-and-chip harvesting (11.87 %), revealing that the influence of the former factor was decisive. Management diagrams that combine the discount rate, yield and biomass price are provided as tools for decision makers. Graphical abstract: Image 1 Highlights: Poplar Short Rotation Coppices could be profitable under appropriate conditions. High productivity and favorable biomass price are key to profitability. Land rent, irrigation and harvesting are the most critical poplar plantation costs. An economic decision-making tool for poplar Short Rotation Coppices is proposed.